Punica granatum L. Juice Attenuates Experimental Cerebral Vasospasm in the Rabbit Subarachnoid Hemorrhage Model: A Basilar Artery Morphometric Study and Apoptosis - GÜVENÇ, YAHYA (THIEME MEDICAL PUBL INC, 2017)
Background This study investigated the effect of Punica granatum L. (pomegranate) juice on the rabbit basilar artery in an experimental subarachnoid hemorrhage (SAH) model. Methods Eighteen adult male New Zealand white rabbits were randomly divided into three groups: a control group (n = 6), SAH group (n = 6), and SAH + treatment group (n = 6). Basilar artery diameter was measured with magnetic resonance angiography (MRA) in all groups at the beginning of the study. Experimental SAH was created by injecting autologous arterial blood into the cisterna magna. In the treatment group, the subjects were administered a daily dose of 30 ml/kg pomegranate juice via gastric gavage for 4 days after the SAH. The SAH group and SAH + treatment group underwent cerebral MRA after 72 hours. After a neurologic score assessment, all the animals were killed. The wall thickness and lumen area of the basilar artery were measured histometrically in all groups, and the apoptotic cell percentage in the artery was identified. The mean diameter of the basilar artery during MRA was measured. Results Pomegranate improved neurologic functions compared with the SAH group (p < 0.01). The mean basilar artery diameter on MRA in the SAH + treatment group was larger than in the SAH group and smaller than in the control group (p < 0.01 and p < 0.05, respectively). The mean vessel wall thickness value in the SAH + treatment group was lower than in the SAH group (p < 0.01), whereas there was no difference between the control and the SAH + treatment group (p > 0.05). The apoptotic cell rate in the SAH + treatment group was significantly lower than in the SAH group (p < 0.001). Evaluation of the basilar artery luminal area showed no difference between the three groups (p > 0.05). Discussion Pomegranate was shown to have a vasospasm-attenuating effect on the basilar artery in the rabbit SAH model for the first time in our study.
Keywords: subarachnoid hemorrhage; pomegranate; vasospasm; treatment; rabbit; POMEGRANATE JUICE; OXIDATIVE STRESS; ELLAGIC ACID; BRAIN-INJURY; IN-VITRO; RATS; CONSUMPTION; EXTRACT; DAMAGE; INFLAMMATION